Improving Student Learning Outcomes in Islamic Education Learning through the Quantum Learning Model at SD Negeri 0110 Hutarimbaru - Lubis, Siti Zubaidah; Nasution, Emmi Rahmi; Lubis, Lisna Wati (Jurnal Profesi Guru Indonesia, 2024)
Classroom Action Research Report Entitled "Improving Students' Learning Outcomes In Islamic Education Learning Through The Quantum Learning Model For Students At State Elementary School 1308 Hutarimbaru In The 2023/2024 Academic Year. This study aims to enhance student learning outcomes in Islamic Education at SD Negeri 1308 Hasahatan Julu through the implementation of the Quantum Learning model. Using a Classroom Action Research (CAR) approach, the research involved 30 fifth-grade students and focused on improving their participation, comprehension, and academic performance. The findings revealed a significant improvement in students' engagement, understanding, and retention of Islamic Education content following the use of the Quantum Learning model. The interactive and student-centered activities encouraged critical thinking, collaboration, and real-life application of Islamic principles, leading to more meaningful learning experiences. In conclusion, the Quantum Learning model proved to be an effective approach for enhancing student achievement and fostering a deeper connection to the subject matter.